Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Development of chicks during extreme cold conditions: the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (University of Ottawa Press, 1988)
Keywords: Dronning Maud Land; fugler; konferanse; kongress; ornitologi; zoologi

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970 - Adie, Raymond J. (International Union of Geological Sciences, 1972)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Report on attendance at the Second Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6 to 15 August, 1970 - Kent, L E (Geological Survey of South Africa, 1971)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium